2011
DOI: 10.1111/j.1365-2761.2010.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of marine salmonid alphavirus subtypes 1–6 using an experimental cohabitation challenge model

Abstract: A comparative challenge study of six marine isolates representing subtypes 1-6 of salmonid alphavirus (salmon pancreas disease virus, Genus Alphavirus, Family Togaviridae) was conducted in Atlantic salmon in a fresh water cohabitation trial. Histopathological lesions typical of pancreas disease were observed with all subtypes, and virus was re-isolated from serum of cohabitant fish in each case. Using a virus neutralization (VN) test neutralizing salmonid alphavirus (SAV) subtype 1 strain F93-125, VN antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 32 publications
(45 reference statements)
8
93
0
Order By: Relevance
“…We hypothesise that viruses other than SAV could be targeting this tissue and may have contributed to the lesions recorded, as no persistent subclinical SAV infection would be detectable by RT-qPCR. A comprehensive cohabitation challenge study by Graham et al (2011) compared isolates from all 6 subtypes using parameters that included lesion score and virus load. In that study the authors demonstrated that there are differences between isolates with regards to replication and shedding dynamics; for example, Subtype V fish were found at a lower frequency than Subtype I and III fish, and virus load was initially lower than in the latter subtypes, but exceeded Subtype I at later times.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that viruses other than SAV could be targeting this tissue and may have contributed to the lesions recorded, as no persistent subclinical SAV infection would be detectable by RT-qPCR. A comprehensive cohabitation challenge study by Graham et al (2011) compared isolates from all 6 subtypes using parameters that included lesion score and virus load. In that study the authors demonstrated that there are differences between isolates with regards to replication and shedding dynamics; for example, Subtype V fish were found at a lower frequency than Subtype I and III fish, and virus load was initially lower than in the latter subtypes, but exceeded Subtype I at later times.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a comparative experimental study in Atlantic salmon, conducted as a freshwater cohabitation trial, showed that all subtypes caused pathological changes typical of PD, although the relative virulence of the strains varied (Graham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that SAV is not a virus specifically infecting salmonids. Cohabitation trials with infected shedders have shown that SAV is certainly horizontally transmitted from fish to fish, so high density aquaculture tanks are ideal for horizontal SAV transmission (Graham et al, 2011 (Fig. 2), and contains a positive, single-stranded RNA genome of around 12 kb, encoding two polyproteins (Villoing et al, 2000).…”
Section: Sav Transmissionmentioning
confidence: 99%
“…At present, at least six different SAV subtypes have been distinguished based on genotype and geographic distribution (Fringuelli et al, 2008;Graham et al, 2012;Graham et al, 2011). Infections may lead up to 48% mortality and deteriorated fillet quality (Lerfall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation